Localized chromophobe renal cell carcinoma: preoperative imaging judgment and laparoscopic simple enucleation for treatment - Ren,Wenbiao (2018)
ABSTRACT Objective: To evaluate the preoperative imaging manifestation and therapeutic effect of laparoscopic simple enucleation (SE) for localized chromophobe renal cell carcinoma (chRCC). Materials and Methods: Clinical data of 36 patients who underwent laparoscopic SE of localized chRCC at our institute were retrospectively analyzed. All patients underwent preoperative renal protocol CT (unenhanced, arterial, venous, and delayed images). CT scan characteristics were evaluated. After intraoperative occlusion of the renal artery, the tumor was free bluntly along the pseudocapsule and enucleated totally. The patients were followed up regularly after the operation. Results: Mean tumor diameter was 3.9±1.0 cm, 80% of tumors were homogeneous and all the tumors had complete pseudocapsule. The attenuation values were slightly lower than normal renal cortex and degree of enhancement of the tumors were significantly lower than normal renal cortex. Mean operation time was 104.3±18.2 min. Mean warm ischemia time (WIT) was 21.3±3.5 min. Mean blood loss was 78.6±25.4 mL. No positive surgical margin was identified. Mean postoperative hospital stay was 5.3±1.5 d. Hematuria occurred in 3 patients and all disappeared within 3 days. After a mean follow-up of 32.1±20.6 months, no patient had local recurrence or metastatic progression. Conclusion: Localized chRCCs have a great propensity for homogeneity and complete pseudocapsule. The attenuation values were slightly lower than normal renal cortex and small degree of enhancement. Laparoscopic SE is a safe and effective treatment for localized chRCC. The oncological results were satisfactory.